1977
DOI: 10.2134/jeq1977.00472425000600030017x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Copper, Zinc, and Cadmium by a Forest Soil

Abstract: Time‐dependent batch equilibrium studies for Cu, Zn, and Cd were conducted to determine the sorbing properties for these metals on the upper 30 cm of a forest soil. Major cations were added to equilibrating solutions in an attempt to match to cationic matrix of a sewage sludge. Essentially all of the Cu was adsorbed by the soil in the first 0.3 hour of equilibration. Copper adsorption data fit the Freundlich isotherm better than the Langmuir isotherm. Adsorption of Zn and Cd was more time dependent than Cu, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, Amarcher et al (1986) were not able to correlate the retention of Cd, Cu, Zn and Pb with iron oxide content. Sidle and Kardos (1997) found a correlation between Cd retention and organic matter content while Harter (1983) could not tie total organic matter content to metal sorption.…”
Section: Introductionmentioning
confidence: 89%
“…However, Amarcher et al (1986) were not able to correlate the retention of Cd, Cu, Zn and Pb with iron oxide content. Sidle and Kardos (1997) found a correlation between Cd retention and organic matter content while Harter (1983) could not tie total organic matter content to metal sorption.…”
Section: Introductionmentioning
confidence: 89%
“…Others (e.g. Heydemann, 1959; Sidle and Kardos, 1977) have found that their data fitted Freundlich isotherms more closely than Langmuir isotherms. Zunino and Martin (1977) used the concept of an adsorption isotherm in their studies of copper complexing by colloidal organic matter.…”
Section: Introductionmentioning
confidence: 96%
“…Anthropogenic sources comprise contributions made by mankind including industrial processes that contribute to both atmospheric and land depositions, mining and metallurgy, urban and industrial wastage, and sewage and fertilizer applications [4]. Soil characteristics positively correlated with Cd retention are pH [5], organic matter (OM) content, cation exchange capacity (CEC) [6], and specific surface area (SSA) [7], while free iron oxides are negatively correlated [8].…”
Section: Introductionmentioning
confidence: 99%